Partial Molecular Characterization of Arctium minus Aspartylendopeptidase and Preparation of Bioactive Peptides by Whey Protein Hydrolysis - Cimino, Cecilia Verónica (2015)
In this article, we report the cloning of an aspartic protease (AP) from flowers of Arctium minus (Hill) Bernh. (Asteraceae) along with the use of depigmented aqueous flower extracts, as a source of APs, for the hydrolysis of whey proteins. The isolated cDNA encoded a protein product with 509 amino acids called arctiumisin, with the characteristic primary structure organization of typical plant APs. Bovine whey protein hydrolysates, obtained employing the enzyme extracts of A. minus flowers, displayed inhibitory angiotensin-converting enzyme (ACE) and antioxidant activities. Hydrolysates after 3 and 5 h of reaction (degree of hydrolysis 2.4 and 5.6, respectively) and the associated peptide fraction with molecular weight below 3 kDa were analyzed by sodium dodecyl sulfate–polyacrylamide gel electrophoresis, matrix-assisted laser desorption ionization/time of flight mass spectrometry, and reverse phase-high-performance liquid chromatography. The results obtained in this study demonstrate the viability of using proteases from A. minus to increase the antioxidant and inhibitory ACE capacity of whey proteins.